Implementation of a Simple Hydroponic System to Enhance Food Security in the Al-Mawaddah Warrahmah Kolaka Islamic High School Environment - Edi Usman; Pardawati; Irmayanti; Aulia Lukman; Jumasrah; Sumarni (PT FORMOSA CENDEKIA GLOBAL, 2024)
A community service activity involving the socialization and implementation of a simple hydroponic system was conducted at Madrasah Aliyah Al Mawaddah Warrahmah Kolaka. The aim of this activity was to enhance understanding of hydroponic technology and food security among the madrasah community, and to implement a simple hydroponic system within the madrasah environment. The methods employed included initial coordination, general socialization, specialized workshops, demonstrations, hands-on practice in building hydroponic systems, and evaluation.. Final evaluation indicated that 95% of participants were satisfied with the activity's implementation, and 85% planned to apply hydroponics at home. This activity successfully laid a strong foundation for developing a hydroponic program in the madrasah, which has the potential to improve food security and educational quality. In conclusion, the socialization and implementation of this simple hydroponic system achieved its objectives successfully, delivering positive impacts for Madrasah Aliyah Al Mawaddah Warrahmah Kolaka and potentially serving as a model for replication in other educational institutions.